Non-aqueous electrolyte secondary battery

By using carbonate-containing electrolytes and silicon-based negative electrodes in nonaqueous electrolyte secondary batteries, the problem of poor performance in existing batteries in cycling, low-temperature charging and high-temperature volume expansion characteristics is solved, and higher battery performance is achieved.

JP2025068892APending Publication Date: 2025-04-30NIPPON SHOKUBAI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023178995
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

When existing nonaqueous electrolyte secondary batteries use silicon-based negative electrodes and base electrolytes, it is difficult to effectively improve battery performance, especially in terms of cycle characteristics, low-temperature charging characteristics and high-temperature volume expansion characteristics.

Method used

A non-aqueous electrolyte solution containing a carbonate component is used as the electrolyte. Specifically, the solution contains carbon dioxide (CO2), carbon monoxide (CO), bicarbonate ions (HCO3-) and carbonate ions (CO32-), and silicon, silicon alloy or silicon oxide is used as the live substance in the negative electrode.

Benefits of technology

The battery performance is significantly improved, including cycle characteristics, low-temperature charging characteristics and high-temperature volume expansion characteristics, which is more significant than traditional batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068892000001
    Figure 2025068892000001
  • Figure 2025068892000002
    Figure 2025068892000002
  • Figure 2025068892000003
    Figure 2025068892000003
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte secondary battery having a Si-based negative electrode and a non-aqueous electrolyte solution having a carbonate component such as CO2 dissolved therein, the battery having a higher effect of improving battery performance due to the dissolved carbonate component compared to conventional batteries.SOLUTION: A non-aqueous electrolyte secondary battery includes a non-aqueous electrolyte solution containing LiN(FSO2)2 and having at least one carbonate component selected from the group consisting of carbon dioxide (CO2), carbon monoxide (CO), bicarbonate ion (HCO3-), and carbonate ion (CO32-) dissolved therein, a negative electrode containing at least one component selected from the group consisting of Si, a Si alloy, and SiO as a negative electrode active material, and a positive electrode, and the total dissolved amount of the carbonate components is 20 ppm by mass or more with respect to 100% by mass of the total amount of components contained in the non-aqueous electrolyte solution.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] In order to improve the performance of secondary batteries such as lithium-ion secondary batteries, various non-aqueous electrolytes and their materials have been investigated for use in secondary batteries. For example, it has been reported that the performance of a battery using a silicon (Si)-based negative electrode can be improved by injecting carbon dioxide (CO2).

[0003] For example, Patent Document 1 proposes a lithium secondary battery comprising a negative electrode in which a mixture layer containing active material particles containing silicon and / or a silicon alloy and a polyimide binder is sintered on the surface of a current collector made of conductive metal foil, a positive electrode, and a non-aqueous electrolyte, in which carbon dioxide is dissolved.

[0004] Patent Document 2 proposes a lithium secondary battery that includes a negative electrode containing silicon as a negative electrode active material, a positive electrode containing a lithium transition metal composite oxide as a positive electrode active material, and a non-aqueous electrolyte, in which lithium carbonate is added to the positive electrode and carbon dioxide is dissolved in the non-aqueous electrolyte.

[0005] Patent Document 3 proposes a lithium secondary battery comprising a negative electrode in which a negative electrode active material layer having a negative electrode active material particle including silicon particles and / or silicon alloy particles and a negative electrode binder is disposed on the surface of a negative electrode current collector, a positive electrode having a positive electrode active material, a separator, and a non-aqueous electrolyte, the non-aqueous electrolyte containing CO2. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2005-190977 A [Patent Document 2] JP 2006-196435 A [Patent Document 3] International Publication No. 2007 / 114168 Summary of the Invention [Problem to be solved by the invention]

[0007] Patent Document 1 describes that dissolving 0.37% by mass (3700 ppm by mass) of carbon dioxide in a LiPF6-based non-aqueous electrolyte suppresses the expansion and contraction of silicon due to charging and discharging, suppresses cracking of silicon particles, and as a result, improves cycle characteristics. However, the effect of improving cycle characteristics by dissolving carbon dioxide in the non-aqueous electrolyte is insufficient. In addition, the battery of Patent Document 1 is expensive because of the sintering process using a polyimide binder.

[0008] Although Patent Document 2 describes that dissolving carbon dioxide in a LiPF6-based non-aqueous electrolyte suppresses the expansion and contraction of silicon particles and improves cycle characteristics, the improvement effect is insufficient, as in Patent Document 1. Furthermore, in the battery of Patent Document 2, the energy density decreases due to the addition of lithium carbonate to the positive electrode.

[0009] Patent Document 3 describes that dissolving CO2 in a LiPF6-based non-aqueous electrolyte improves cycle characteristics, but similar to Patent Document 1, the improvement effect is insufficient.

[0010] As described above, the conventional batteries having a Si-based negative electrode and a LiPF6-based non-aqueous electrolyte solution as described in Patent Documents 1 to 3 have the disadvantage that the effect of improving battery performance by dissolving CO2 in the non-aqueous electrolyte solution cannot be fully obtained.

[0011] The present disclosure has been made in consideration of the above points, and an object of the present disclosure is to provide a nonaqueous electrolyte secondary battery including a Si-based negative electrode and a nonaqueous electrolyte having dissolved therein a carbonate component such as CO2, in which the effect of improving battery performance by dissolving the carbonate component is greater than that of conventional batteries. [Means for solving the problem]

[0012] The present inventors have conducted extensive research to achieve the above object, and have found that in non-aqueous electrolyte secondary batteries having a Si-based negative electrode and a non-aqueous electrolyte solution containing dissolved carbonate components such as CO2, a non-aqueous electrolyte secondary battery containing a sulfonylimide compound such as LiN(FSO2)2 (hereinafter also referred to as "LiFSI") has a higher effect of improving cycle characteristics, low-temperature charging characteristics, and high-temperature volume expansion characteristics by dissolving the carbonate components than a conventional LiPF6-based non-aqueous electrolyte secondary battery that does not contain a sulfonylimide compound. The present disclosure is specifically as follows.

[0013] In this specification, a high improvement effect on battery performance such as cycle characteristics means that a battery having the same constituent materials except for the reference electrolyte containing dissolved CO2 has a high degree of improvement (improvement rate) compared to a battery having a type of nonaqueous electrolyte (reference electrolyte).

[0014] However, Patent Documents 1 to 3 do not specifically describe a nonaqueous electrolyte secondary battery having a Si-based negative electrode and a nonaqueous electrolyte containing a sulfonylimide compound, and do not discuss the characteristics of the battery. In addition, Patent Documents 1 to 3 do not describe or discuss low-temperature charging characteristics.

[0015] The nonaqueous electrolyte secondary battery of the present disclosure comprises: · Contains LiN(FSO2)2 and also contains carbon dioxide (CO2), carbon monoxide (CO), bicarbonate ion (HCO3 - ) and carbonate ion (CO3 2- A non-aqueous electrolyte solution having at least one carbonate component dissolved therein, a negative electrode containing at least one material selected from the group consisting of Si, a Si alloy, and SiO as a negative electrode active material; A positive electrode and The total dissolved amount of the carbonate components is 20 ppm by mass or more relative to 100% by mass of the total amount of the components contained in the nonaqueous electrolyte.

[0016] In the nonaqueous electrolyte secondary battery of the present disclosure, the content of LiN(FSO2)2 may be 1 mol% or more relative to 100 mol% of the total amount of electrolyte salts contained in the nonaqueous electrolyte, and the content of at least one selected from the group consisting of Si, Si alloy, and SiO may be 5 mass% or more relative to 100 mass% of the total amount of the negative electrode active material. Effect of the Invention

[0017] According to the present disclosure, it is possible to provide a nonaqueous electrolyte secondary battery including a Si-based negative electrode and a nonaqueous electrolyte having dissolved therein a carbonate component such as CO2, in which the effect of improving battery performance by dissolving the carbonate component is greater than that of conventional batteries. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present embodiment will be described in detail below. The following description of the preferred embodiment is merely exemplary in nature and is not intended to limit the present invention, its application, or its uses.

[0019] <Nonaqueous electrolyte secondary battery> The nonaqueous electrolyte secondary battery according to this embodiment is a secondary battery including a nonaqueous electrolyte, a negative electrode, and a positive electrode.

[0020] [Non-aqueous electrolyte] The non-aqueous electrolyte contains an electrolyte salt and has a carbonate component dissolved therein.

[0021] (Electrolyte salt) The non-aqueous electrolyte contains lithium bis(fluorosulfonyl)imide [LiN(FSO2)2, LiFSI, sulfonylimide compound] as an electrolyte salt (lithium salt). LiFSI may be present (contained) in the form of ions in the non-aqueous electrolyte. LiFSI may be a commercially available product, or may be synthesized by a conventional method.

[0022] The lower limit of the LiFSI concentration in the non-aqueous electrolyte is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, even more preferably 0.1 mol / L or more, even more preferably 0.2 mol / L or more, and even more preferably 0.5 mol / L or more, from the viewpoint of enhancing the effect of improving battery performance by dissolving a carbonate component in the non-aqueous electrolyte. The upper limit of the concentration is preferably 5 mol / L or less, more preferably 3 mol / L or less, and even more preferably 2 mol / L or less, from the viewpoint of suppressing a decrease in battery performance due to an increase in the viscosity of the electrolyte.

[0023] The lower limit of the LiFSI content in the non-aqueous electrolyte is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, even more preferably 10 mol% or more, and even more preferably 20 mol% or more, based on 100 mol% of the total electrolyte salts contained in the non-aqueous electrolyte, from the viewpoint of enhancing the effect of improving battery performance by dissolving a carbonate component in the non-aqueous electrolyte. The upper limit of the content may be 100 mol% (single salt containing only LiFSI) based on 100 mol% of the total electrolyte salts contained in the non-aqueous electrolyte, and is preferably 80 mol% or less, more preferably 50 mol% or less, based on 100 mol% of the total electrolyte salts contained in the non-aqueous electrolyte, from the viewpoint of suppressing a decrease in battery performance due to an increase in the viscosity of the electrolyte.

[0024] The lower limit of the content of LiFSI in the non-aqueous electrolyte is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, even more preferably 1% by mass or more, even more preferably 3% by mass or more, and particularly preferably 5% by mass or more, based on the total amount of the components contained in the non-aqueous electrolyte (based on 100% by mass) of the non-aqueous electrolyte, from the viewpoint of enhancing the effect of improving the battery performance by dissolving a carbonate component in the non-aqueous electrolyte. The upper limit of the content may be 100% by mass (single salt containing only LiFSI) based on 100% by mass of the total amount of the components contained in the non-aqueous electrolyte, and is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, even more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the viewpoint of suppressing the deterioration of the battery performance due to the increase in the viscosity of the electrolyte.

[0025] The non-aqueous electrolyte may contain LiFSI as an electrolyte salt, but may contain other electrolyte salts such as other sulfonylimide compounds, imide salts, non-imide salts, etc., in addition to LiFSI, as necessary. The other electrolyte salts may be used alone, or two or more of them may be used in combination. The other electrolyte salts may be present (contained) in the form of ions in the non-aqueous electrolyte. The other electrolyte salts may be commercially available products, or may be synthesized by a conventional method.

[0026] Other sulfonylimide compounds include, for example, lithium (fluorosulfonyl) (methylsulfonyl) imide, lithium (fluorosulfonyl) (ethylsulfonyl) imide, lithium (fluorosulfonyl) (trifluoromethylsulfonyl) imide, lithium (fluorosulfonyl) (pentafluoroethylsulfonyl) imide, lithium (fluorosulfonyl) (heptafluoropropylsulfonyl) imide, and the like.

[0027] LiFSI and other sulfonylimide compounds are collectively represented by the general formula (1): [C1] LiN(RSO2)(FSO2)···(1) It can also be expressed as:

[0028] In general formula (1), R represents a fluorine atom, an alkyl group having 1 to 6 carbon atoms, or a fluoroalkyl group having 1 to 6 carbon atoms.

[0029] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, and a hexyl group. Among the alkyl groups having 1 to 6 carbon atoms, a linear or branched alkyl group having 1 to 6 carbon atoms is preferred, and a linear alkyl group having 1 to 6 carbon atoms is more preferred.

[0030] Examples of the fluoroalkyl group having 1 to 6 carbon atoms include an alkyl group having 1 to 6 carbon atoms in which some or all of the hydrogen atoms have been substituted with fluorine atoms. Examples of the fluoroalkyl group having 1 to 6 carbon atoms include a fluoromethyl group, a difluoromethyl group, a trifluoromethyl group, a fluoroethyl group, a difluoroethyl group, a trifluoroethyl group, and a pentafluoroethyl group. In particular, the fluoroalkyl group may be a perfluoroalkyl group.

[0031] The substituent R is preferably a fluorine atom or a perfluoroalkyl group (for example, a perfluoroalkyl group having 1 to 6 carbon atoms, such as a trifluoromethyl group, a pentafluoroethyl group, or a heptafluoropropyl group), more preferably a fluorine atom, a trifluoromethyl group, or a pentafluoroethyl group, still more preferably a fluorine atom or a trifluoromethyl group, and even more preferably a fluorine atom.

[0032] Examples of the imide salt include fluorine-containing sulfonylimide salts other than sulfonylimide compounds. Examples of the imide salt include non-lithium salts of the fluorine-containing sulfonylimide listed as sulfonylimide compounds (for example, salts in which lithium (ion) in the sulfonylimide compound is replaced with a cation other than lithium ion). Examples of salts in which a cation other than lithium ion is replaced include alkali metal salts such as sodium salts, potassium salts, rubidium salts, and cesium salts; alkaline earth metal salts such as beryllium salts, magnesium salts, calcium salts, strontium salts, and barium salts; aluminum salts; ammonium salts; and phosphonium salts.

[0033] Examples of the non-imide salt include salts of non-imide anions and cations (lithium ions and the above-listed cations). [Case 2] LiPF a (C m F 2m+1 ) 6-a (a:0≦a≦6, m:1≦m≦4)···(2) (hereinafter referred to as "fluorophosphate compound (2)") represented by general formula (3): [C3] LiBF b (C n F 2n+1 ) 4-b (b:0≦b≦4, n:1≦n≦4)···(3) (hereinafter referred to as "fluoroborate compound (3)"), lithium salts such as lithium hexafluoroarsenate (LiAsF6), LiSbF6, LiClO4, LiSCN, LiAlF4, CF3SO3Li, LiC[(CF3SO2)3], LiN(NO2), LiN[(CN)2], etc.; non-lithium salts (for example, salts in which the lithium (ion) in these lithium salts is substituted with the cations exemplified above (for example, NaBF4, NaPF6, NaPF3(CF3)3, etc.), etc.).

[0034] Examples of the fluorophosphate compound (2) include LiPF6, LiPF3(CF3)3, LiPF3(C2F5)3, LiPF3(C3F7)3, LiPF3(C4F9)3, etc. Among the fluorophosphate compounds (2), LiPF6 is preferred.

[0035] Examples of the fluoroboric acid compound (3) include LiBF4, LiBF(CF3)3, LiBF(C2F5)3, LiBF(C3F7)3, etc. Among the fluoroboric acid compounds (3), LiBF4 is preferred.

[0036] Among the other electrolyte salts, from the viewpoints of ionic conductivity, cost, and the like, non-imide salts are preferred, and the fluorophosphate compound (2), fluoroboric acid compound (3) and LiAsF6 are more preferred, with the fluorophosphate compound (2) being more preferred.

[0037] The electrolyte salt may have a composition containing LiFSI alone or a composition containing LiFSI and another electrolyte salt. When using an electrolyte salt having a mixed salt composition, an electrolyte salt having a mixed salt composition containing LiFSI and a fluorophosphate compound (2) is preferred, and an electrolyte salt having a mixed salt composition containing LiFSI and LiPF6 is more preferred.

[0038] When using an electrolyte salt of a mixed salt composition containing LiFSI and other electrolyte salts, the lower limit of the concentration of the other electrolyte salts in the non-aqueous electrolyte (the total of the concentrations when two or more kinds are used in combination) is preferably 0.1 mol / L or more, more preferably 0.2 mol / L or more, even more preferably 0.5 mol / L or more, even more preferably 0.7 mol / L or more, and even more preferably 1 mol / L or more from the viewpoint of preventing corrosion of the current collector and enhancing the effect of improving battery performance by dissolving a carbonate component in the non-aqueous electrolyte. The upper limit of the concentration is preferably 5 mol / L or less, more preferably 3 mol / L or less, even more preferably 2 mol / L or less, and even more preferably 1.5 mol / L or less from the viewpoint of suppressing the deterioration of battery performance due to the increase in the viscosity of the electrolyte.

[0039] From the viewpoint of enhancing the effect of improving battery performance by dissolving a carbonate component in the nonaqueous electrolyte, it is preferable to increase the LiFSI concentration. The LiFSI:other electrolyte salt (molar ratio of LiFSI concentration to other electrolyte salt concentration) is preferably 1:25 or more, more preferably 1:10 or more, even more preferably 1:8 or more, even more preferably 1:5 or more, even more preferably 1:2 or more, and particularly preferably 1:1 or more. Moreover, from the viewpoint of preventing corrosion of the current collector, the molar ratio is preferably 10:1 or less, more preferably 2:1 or less.

[0040] The lower limit of the total concentration of the electrolyte salt in the nonaqueous electrolyte is preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, even more preferably 1 mol / L or more, and even more preferably 1.2 mol / L or more, from the viewpoint of improving the battery performance. The upper limit of the concentration is preferably 5 mol / L or less, more preferably 3 mol / L or less, and even more preferably 2 mol / L or less, from the viewpoint of suppressing the deterioration of the battery performance due to the increase in the electrolyte viscosity.

[0041] (Carbonated component) The nonaqueous electrolyte has a carbonate component dissolved therein. Specifically, the nonaqueous electrolyte constituting the nonaqueous electrolyte secondary battery according to this embodiment is a nonaqueous electrolyte containing LiFSI and having 20 mass ppm or more of a carbonate component dissolved therein (hereinafter, also referred to as a "carbonate component-dissolved electrolyte"). In other words, the carbonate component can be considered as a type of additive for the nonaqueous electrolyte.

[0042] In this specification, dissolution of a carbonate component in a non-aqueous electrolyte means intentionally dissolving a carbonate component in the non-aqueous electrolyte, but does not exclude, for example, a carbonate component contained in a raw material of the non-aqueous electrolyte, such as an electrolyte solvent described below, or a carbonate component that is inevitably dissolved in the non-aqueous electrolyte in a normal manufacturing process of the non-aqueous electrolyte or a secondary battery. In other words, the total dissolved amount of the carbonate components described below may include the carbonate component intentionally dissolved, as well as the carbonate component in the raw material and the carbonate component that is inevitably dissolved.

[0043] Examples of carbonic acid components include carbon dioxide (CO2), carbon monoxide (CO), and bicarbonate ions (HCO3 - ), carbonate ion (CO3 2- The carbonate component may be used alone or in combination of two or more. The form of the carbonate component dissolved in the non-aqueous electrolyte is not particularly limited, and may be CO2, CO, HCO3, etc. - and CO3 2- It is sufficient that the compound is present in at least one of the above forms, and it may be present in any one of the above forms, or may be present in a plurality of forms.

[0044] The lower limit of the total dissolved amount of the carbonate component in the non-aqueous electrolyte is 20 mass ppm or more, preferably 50 mass ppm or more, more preferably 100 mass ppm or more, even more preferably 150 mass ppm or more, even more preferably 200 mass ppm or more, and particularly preferably 250 mass ppm or more, in terms of the non-aqueous electrolyte ratio (relative to 100 mass% of the total amount of the components contained in the non-aqueous electrolyte), from the viewpoint of enhancing the effect of improving the battery performance by dissolving the carbonate component in the non-aqueous electrolyte. The upper limit of the total dissolved amount is not particularly limited as long as it is equal to or less than the saturation concentration at a predetermined temperature (such as 25°C), and is, for example, 5000 mass ppm or less, 4500 mass ppm or less, 4000 mass ppm or less, 3500 mass ppm or less, etc., relative to 100 mass% of the total amount of the components contained in the non-aqueous electrolyte. The total dissolved amount can be measured by a method described in the examples below, for example, gas chromatography, etc.

[0045] In this specification, the total amount of dissolved carbonic acid components in the nonaqueous electrolyte solution means In the preparation process of the nonaqueous electrolyte, the total amount of dissolved carbonate components in the electrolyte immediately after preparation, or after an aging period (e.g., one week) has elapsed to stabilize the amount of dissolved carbonate components, if necessary; or This refers to the total amount of dissolved carbonate components in the electrolyte extracted from a battery, for example in a nitrogen atmosphere, after the battery has been aged during the manufacturing process of the secondary battery.

[0046] The aging step may be, for example, the following steps or the conditioning conditions described in the Examples below. (I) After electrolyte injection and partial charging, the battery is subjected to high temperature treatment (storage) at 30°C or higher for at least 6 hours for a period of up to 28 days. After degassing and resealing, the battery is checked for initial performance defects by charging and discharging, and then kept at 50% charge for at least one week to check for defects due to self-discharge. (II) The same process as (I) except that the high temperature treatment is not performed after the partial charge. (III) A process similar to (I) except that degassing is not performed after the high-temperature treatment.

[0047] Examples of the method for dissolving a carbonic acid component in the nonaqueous electrolyte include the following methods. (A) A method in which a carbonic acid component is dissolved in the non-aqueous electrolyte during the preparation of the non-aqueous electrolyte. (B) A method of dissolving a carbonic acid component in a non-aqueous electrolyte during the production process of a secondary battery.

[0048] (A) In the preparation step of the non-aqueous electrolyte, the method of dissolving a carbonate component in the non-aqueous electrolyte is, in other words, a method of using an electrolyte containing LiFSI and having a predetermined amount of carbonate component dissolved therein in advance, and injecting the electrolyte into a secondary battery. Examples of the method of dissolving a carbonate component in the non-aqueous electrolyte (dissolving step) include a method of contacting a gas containing a carbonate component with the non-aqueous electrolyte (contacting step), a method of blowing a gas containing a carbonate component into the non-aqueous electrolyte (bubbling step), a method of stirring the non-aqueous electrolyte under a gas atmosphere containing a carbonate component (stirring step), a method of contacting a high-pressure gas containing a carbonate component with the non-aqueous electrolyte (a method of pressurizing a gas containing a carbonate component into the non-aqueous electrolyte, pressurizing step), and a method of adding a substance that generates a gas containing a carbonate component to the non-aqueous electrolyte (adding step). Examples of the substance that generates a gas containing a carbonate component include bicarbonate, carbonate, dry ice, etc. In addition, since the carbonic acid component can be dissolved in an electrolyte solvent generally used for a non-aqueous electrolyte, the non-aqueous electrolyte may be prepared by dissolving LiFSI in an electrolyte solvent in which the carbonic acid component has been dissolved in advance. The method of dissolving the carbonic acid component in the electrolyte solvent can be the same as that described above. As another method, a non-aqueous electrolyte prepared in advance is placed in a sealed container so that the volume is about 1 / 10 of the volume of the container, and the container is made into a substantially vacuum state, and then filled with the carbonic acid component. This operation is repeated several times to replace the air in the container with the carbonic acid component, and finally the container is sealed and stored at a low temperature for several days (substitution step). The dissolving step may include at least one of the above steps, and may be a combination of multiple steps. In the dissolving step, it is preferable to include at least one of a pressurizing step, a liquid contact step, a bubbling step, and a substitution step, and it is more preferable to include at least one of a pressurizing step and a substitution step, and a pressurizing step and a substitution step (which may be a combination of a pressurizing step and a substitution step) are even more preferable.

[0049] In the method (A), from the viewpoint of controlling the total amount of dissolved carbonic acid components in the nonaqueous electrolyte to a constant amount, the secondary battery may be assembled in a CO2 atmosphere or an atmosphere containing CO2. Specifically, the step of injecting the nonaqueous electrolyte having dissolved therein carbonic acid components into the battery and the steps after the injection may be performed in a CO2 atmosphere or an atmosphere containing CO2. After the injection of the electrolyte, the battery may be exposed to a high-pressure CO2 atmosphere.

[0050] (B) In the manufacturing process of a secondary battery, examples of the method of dissolving a carbonate component in a non-aqueous electrolyte include a method of assembling a secondary battery under a CO2 atmosphere and injecting a non-aqueous electrolyte into the battery (specifically, a method of creating a nearly vacuum state inside a laminated battery exterior sealed on three sides, filling it with CO2, and then injecting a non-aqueous electrolyte from the unsealed side and sealing it at normal pressure); a method of injecting a non-aqueous electrolyte into a secondary battery and then replacing the air in the battery with CO2, and the like. The method of replacing the air in the battery with CO2 can be the same as the method of replacing the air in the container with CO2. Specifically, the operation of creating a nearly vacuum state inside the exterior in which a non-aqueous electrolyte has been injected, and then filling it with CO2 is repeated several times, thereby replacing the air in the exterior with CO2.

[0051] In addition, since the total amount of carbonate components dissolved in the nonaqueous electrolyte varies depending on the temperature of the nonaqueous electrolyte, it is preferable that the temperature is controlled to a constant value in the process of preparing the nonaqueous electrolyte and / or in the process of producing the secondary battery.

[0052] (Electrolyte Solvent) The non-aqueous electrolyte may contain an electrolyte solvent, and preferably contains a carbonate-based solvent as the electrolyte solvent. Examples of carbonate solvents include chain carbonate (carbonic acid ester) solvents such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), diphenyl carbonate, and methyl phenyl carbonate; saturated cyclic carbonate solvents such as ethylene carbonate (EC), propylene carbonate (PC), 2,3-dimethylethylene carbonate, 1,2-butylene carbonate, and erythritan carbonate; cyclic carbonate solvents having unsaturated bonds such as vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, 2-vinylethylene carbonate, and phenylethylene carbonate; and fluorine-containing cyclic carbonate solvents such as fluoroethylene carbonate (FEC), 4,5-difluoroethylene carbonate, and trifluoropropylene carbonate. The carbonate-based solvents may be used alone or in combination of two or more. Among the carbonate-based solvents, those containing at least one selected from the group consisting of chain carbonate-based solvents and saturated cyclic carbonate-based solvents are preferred, a mixed solvent containing a chain carbonate-based solvent and a saturated cyclic carbonate-based solvent is more preferred, and a mixed solvent containing EMC and EC is even more preferred.

[0053] From the viewpoint of enhancing the effect of improving battery performance by dissolving a carbonic acid component in the nonaqueous electrolyte, the lower limit of the content of the carbonate-based solvent is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on 100% by mass of the total amount of the electrolyte solvent. The upper limit of the content may be 100% by mass (electrolyte solvent containing only carbonate-based solvent) based on 100% by mass of the total amount of the electrolyte solvent.

[0054] The non-aqueous electrolyte may contain a carbonate-based solvent, but may also contain other electrolyte solvents. The other electrolyte solvents are not particularly limited as long as they can dissolve and disperse the electrolyte salt, and include non-aqueous solvents other than carbonate-based solvents, and any solvent generally used in batteries can be used.

[0055] As the non-aqueous solvent (excluding carbonate-based solvents) used as the other electrolyte solvent, a solvent having a large dielectric constant, high solubility of the electrolyte, a boiling point of 60° C. or more, and a wide electrochemical stability range is preferable. More preferably, it is an organic solvent having a low water content. Examples of such organic solvents include ether-based solvents such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydropyran, crown ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,4-dioxane, and 1,3-dioxolane; aromatic carboxylate-based solvents such as methyl benzoate and ethyl benzoate; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; phosphate-based solvents such as trimethyl phosphate, ethyl dimethyl phosphate, diethyl methyl phosphate, and triethyl phosphate; acetonitrile, ... Examples of the solvent include nitrile solvents such as tolyl, propionitrile, methoxypropionitrile, glutaronitrile, adiponitrile, 2-methylglutaronitrile, valeronitrile, butyronitrile, and isobutyronitrile; sulfur compound solvents such as dimethylsulfone, ethylmethylsulfone, diethylsulfone, sulfolane, 3-methylsulfolane, and 2,4-dimethylsulfolane; aromatic nitrile solvents such as benzonitrile and tolunitrile; nitromethane, 1,3-dimethyl-2-imidazolidinone, 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone, and 3-methyl-2-oxazolidinone; and chain ester solvents such as ethyl acetate, butyl acetate, and propyl propionate. These solvents may be used alone or in combination of two or more.

[0056] The non-aqueous electrolyte may be used as a medium such as a polymer or polymer gel used in place of the electrolyte solvent. When a polymer or polymer gel is used in place of the electrolyte solvent, the following methods may be adopted. That is, a method of dropping a solution in which an electrolyte salt is dissolved in an electrolyte solvent onto a polymer formed into a film by a conventionally known method to impregnate and support the electrolyte salt and the electrolyte solvent; a method of melting and mixing a polymer and an electrolyte salt at a temperature equal to or higher than the melting point of the polymer, forming a film, and impregnating the electrolyte solvent therein (above, gel electrolyte); a method of mixing a non-aqueous electrolyte in which an electrolyte salt is dissolved in an electrolyte solvent in advance with a polymer, forming a film by a casting method or a coating method, and volatilizing the electrolyte solvent; a method of melting a polymer and an electrolyte salt at a temperature equal to or higher than the melting point of the polymer, mixing them, and forming them (true polymer electrolyte), etc.

[0057] Examples of polymers that can be used in place of the electrolyte solvent include polyethylene oxide (PEO), which is a homopolymer or copolymer of epoxy compounds (ethylene oxide, propylene oxide, butylene oxide, allyl glycidyl ether, etc.), polyether-based polymers such as polypropylene oxide, methacrylic polymers such as polymethyl methacrylate (PMMA), nitrile-based polymers such as polyacrylonitrile (PAN), fluorine-based polymers such as polyvinylidene fluoride (PVdF) and polyvinylidene fluoride-hexafluoropropylene, and copolymers thereof. These polymers may be used alone or in combination of two or more.

[0058] (Additives) The non-aqueous electrolyte may further contain an additive for improving various characteristics of the lithium ion secondary battery. The additive may be added to the non-aqueous electrolyte or may be added during the preparation process of the non-aqueous electrolyte.Examples of additives include carboxylic acid anhydrides such as succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, diglycolic anhydride, cyclohexanedicarboxylic anhydride, cyclopentanetetracarboxylic dianhydride, and phenylsuccinic anhydride; sulfur-containing compounds such as ethylene sulfite, 1,3-propane sultone, 1,4-butane sultone, methyl methanesulfonate, busulfan, sulfolane, sulfolene, dimethyl sulfone, tetramethylthiuram monosulfide, and trimethylene glycol sulfate; Yellow compounds; nitrogen-containing compounds such as 1-methyl-2-pyrrolidinone, 1-methyl-2-piperidone, 3-methyl-2-oxazolidinone, 1,3-dimethyl-2-imidazolidinone, and N-methylsuccinimide; saturated hydrocarbon compounds such as heptane, octane, and cycloheptane; carbonate compounds such as vinylene carbonate, fluoroethylene carbonate (FEC), trifluoropropylene carbonate, phenylethylene carbonate, and erythritan carbonate; sulfamic acid (amidosulfuric acid, H3NSO3); sulfamate salts ( Alkaline metal salts such as lithium salts, sodium salts, and potassium salts; alkaline earth metal salts such as calcium salts, strontium salts, and barium salts; other metal salts such as manganese salts, copper salts, zinc salts, iron salts, cobalt salts, and nickel salts; ammonium salts; guanidine salts, etc.; fluorosulfonic acid compounds such as lithium fluorosulfonate (LiFSO3), sodium fluorosulfonate (NaFSO3), potassium fluorosulfonate (KFSO3), and magnesium fluorosulfonate (Mg(FSO3)2); lithium monofluorophosphate (Li2PO3F fluorophosphate compounds such as lithium difluorophosphate (LiPO2F2) and the like; and fluorooxalate compounds such as lithium salts having an oxalic acid skeleton, such as lithium bis(oxalato)borate (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorooxalatophosphate (LIDFOP), lithium tetrafluorooxalatophosphate (LITFOP), lithium difluorobis(oxalato)phosphate (LiDFBOP), and lithium tris(oxalato)phosphate. These additives may be used alone or in combination of two or more.

[0059] The additive is used in an amount of preferably 0.1% by mass to 10% by mass, more preferably 0.2% by mass to 8% by mass, and even more preferably 0.3% by mass to 5% by mass, based on 100% by mass of the total amount of the components contained in the non-aqueous electrolyte. If the amount of additive used is too small, it may be difficult to obtain the effect derived from the additive, while if a large amount of additive is used, it may be difficult to obtain an effect commensurate with the amount added, and the viscosity of the non-aqueous electrolyte may increase, resulting in a decrease in conductivity.

[0060] As described above, the nonaqueous electrolyte constituting the nonaqueous electrolyte secondary battery according to this embodiment is composed of the essential components of LiFSI and carbonate component, and other components such as other electrolyte salts, electrolyte solvents, and additives as necessary. The method for producing the nonaqueous electrolyte (preparation process) is not particularly limited, and the nonaqueous electrolyte can be prepared by mixing these components in a predetermined composition (mass) ratio, for example, the method described in the examples below. Subsequently, a carbonate component is dissolved in the prepared nonaqueous electrolyte by the above method (A) and / or (B), thereby obtaining a carbonate component-dissolved electrolyte.

[0061] [Negative electrode] The negative electrode includes a negative electrode current collector and a negative electrode mixture layer, and the negative electrode mixture layer is formed on the negative electrode current collector and is usually formed into a sheet shape.

[0062] Examples of metals used for the negative electrode current collector include iron, copper, aluminum, nickel, stainless steel (SUS), titanium, tantalum, gold, platinum, etc. Among these, copper is preferred. The shape and dimensions of the negative electrode current collector are not particularly limited.

[0063] The negative electrode mixture layer is formed from a negative electrode mixture (negative electrode composition) that contains a negative electrode active material, a conductive assistant (conductive material), a binder, a solvent for dispersing these components, and the like.

[0064] Here, the nonaqueous electrolyte secondary battery according to this embodiment is composed of a silicon (Si)-based negative electrode. Specifically, the Si-based negative electrode refers to a negative electrode containing at least one selected from the group consisting of Si, Si alloys, and SiO (hereinafter collectively referred to as "Si-based negative electrode active material"). Examples of Si alloys include SiC. The Si-based negative electrode active materials may be used alone or in combination of two or more kinds. The Si-based negative electrode active material may be a commercially available product, or may be obtained by synthesis using a conventionally known method.

[0065] The lower limit of the content of the Si-based negative electrode active material (the content ratio of Si, the total content of each when a plurality of Si-based negative electrode active materials are included) is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, even more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on 100% by mass of the total amount of the negative electrode active material. The upper limit of the content may be 100% by mass (negative electrode active material containing only Si-based negative electrode active material) based on 100% by mass of the total amount of the negative electrode active material, and is preferably 50% by mass or less from the viewpoint of improving the cycle characteristics. Note that the improvement of the cycle characteristics here means an improvement in the capacity retention rate after the cycle test, and is different from increasing the improvement rate (improvement effect) of the cycle characteristics described above.

[0066] The negative electrode active material may contain a Si-based negative electrode active material, but may also contain other negative electrode active materials. As the other negative electrode active material, a conventionally known negative electrode active material used in various batteries (for example, lithium secondary batteries) and the like may be used, and any material capable of absorbing and releasing lithium ions may be used. As the other negative electrode active material, for example, graphite materials (graphite) such as artificial graphite and natural graphite; carbon materials such as mesophase sintered bodies made from coal and petroleum pitch, and non-graphitizable carbon; Sn-based negative electrode materials such as Sn alloys; and lithium alloys such as lithium metal and lithium-aluminum alloys may be used. The other negative electrode active materials may be used alone or in combination of two or more kinds.

[0067] The conductive assistant is used to improve the output of the lithium ion secondary battery. As the conductive assistant, conductive carbon is mainly used. Examples of conductive carbon include carbon black, fibrous carbon (carbon fiber), and graphite. The conductive assistant may be used alone or in combination of two or more kinds. Among the conductive assistants, carbon fiber and carbon black are preferable. Examples of carbon black include ketjen black and acetylene black. The content of the conductive assistant in the non-volatile matter of the negative electrode mixture is preferably 1 to 20 mass %, more preferably 1.5 to 10 mass %, from the viewpoint of improving the output characteristics and electrical characteristics of the lithium ion secondary battery.

[0068] Examples of the binder include fluororesins such as polyvinylidene fluoride (polyvinylidene fluoride, PVdF) and polytetrafluoroethylene; synthetic rubbers such as styrene-butadiene rubber (SBR) and nitrile butadiene rubber; polyamide resins such as polyamideimide; polyolefin resins such as polyethylene and polypropylene; poly(meth)acrylic resins; polyacrylic acid; and cellulose resins such as carboxymethylcellulose (CMC). Each of the binders may be used alone, or two or more types may be used in combination. The binder may be dissolved in a solvent or dispersed in a solvent when used.

[0069] Examples of the solvent include N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, tetrahydrofuran, acetonitrile, acetone, ethanol, ethyl acetate, and water. The solvents may be used alone or in combination of two or more. The amount of the solvent used is not particularly limited and may be appropriately determined depending on the production method and the materials used.

[0070] The negative electrode mixture may contain, as other components as necessary, for example, non-fluorine-based polymers such as (meth)acrylic polymers, nitrile polymers, and diene polymers; polymers such as fluorine-based polymers such as polytetrafluoroethylene; emulsifiers such as anionic emulsifiers, nonionic emulsifiers, and cationic emulsifiers; dispersants such as polymer dispersants such as styrene-maleic acid copolymers and polyvinylpyrrolidone; thickeners such as carboxymethylcellulose, hydroxyethylcellulose, polyvinyl alcohol, polyacrylic acid (salt), and alkali-soluble (meth)acrylic acid-(meth)acrylic acid ester copolymers; preservatives, etc. The content of other components in the non-volatile content of the negative electrode mixture is preferably 0 to 15% by mass, more preferably 0 to 10% by mass.

[0071] The negative electrode mixture can be prepared, for example, by mixing the negative electrode active material, the conductive assistant, the binder, the solvent, and other components as necessary, and dispersing the mixture using a bead mill, a ball mill, an agitator mixer, or the like.

[0072] [Positive electrode] The positive electrode includes a positive electrode current collector and a positive electrode mixture layer. The positive electrode mixture layer is formed on the positive electrode current collector and is usually formed into a sheet shape.

[0073] The metal used for the positive electrode current collector may be any of the metals used for the negative electrode current collector. Among these, aluminum is preferred. The shape and dimensions of the positive electrode current collector are not particularly limited.

[0074] The positive electrode mixture layer is formed from a positive electrode mixture (positive electrode composition). The positive electrode mixture contains a positive electrode active material, a conductive assistant (conductive material), a binder, a solvent for dispersing these components, and the like. Note that the conductive assistant, binder, solvent, and the like can be the same components as those in the negative electrode mixture. The proportions of the components used are also the same as those in the negative electrode mixture.

[0075] The positive electrode active material only needs to be capable of occluding and releasing lithium ions. For example, the positive electrode active materials used in conventionally known lithium ion secondary batteries can be used. The positive electrode active materials may be used alone or in combination of two or more kinds. As the positive electrode active material, commercially available products may be used, or those obtained by synthesis by a conventionally known method may be used. Examples of the positive electrode active material include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) and other ternary positive electrode active materials; olivine-structured iron phosphate-based positive electrode active materials such as LiFePO4, LiFe 0.995 Mn 0.005 PO4 can be preferably used. Among the positive electrode active materials, ternary positive electrode active materials and iron phosphate-based positive electrode active materials (including at least one of ternary positive electrode active materials and iron phosphate-based positive electrode active materials) are preferred, and ternary positive electrode active materials are preferred.

[0076] Among the ternary positive electrode active materials, the general formula (4): [Chemical formula 4] Li v Ni x Co y Mn z O 2+w 〔0.2 ≤ v ≤ 1.2, 0.5 ≤ x ≤ 0.9, 0 < y ≤ 0.3, 0 < z ≤ 0.4, x + y + z = 1, -0.2 ≤ w ≤ 0.2 (v represents the molar ratio of Li, x represents the molar ratio of Ni, y represents the molar ratio of Co, z represents the molar ratio of Mn, and w(2 + w) represents the molar ratio of O).〕···(4) The high-Ni-containing ternary positive electrode active material represented by (hereinafter referred to as "high-Ni-containing ternary positive electrode active material (4)") is preferred.

[0077] In the high Ni-containing ternary positive electrode active material (4), the content ratio of Ni ("x" in the general formula (5)) relative to the total amount 100% (100 mol%) of the transition metals on a molar basis is 50% or more (0.5≦x), preferably 55% or more (0.55≦x), and more preferably 70% or more (0.7≦x). The upper limit of the content ratio is 90% or less (x≦0.9), preferably less than 85% (x<0.85), and more preferably 80% or less (x≦0.8). The content ratios of each component other than Ni in the high Ni-containing ternary positive electrode active material (4) ("v", "y", "z", and "w" (2+w) in the general formula (4)) may be appropriately adjusted within the range of each of the molar ratios. Examples of the high Ni-containing ternary positive electrode active material (4) include the above-mentioned NCM523, NCM622, and NCM811.

[0078] The positive electrode may contain a positive electrode active material other than the ternary positive electrode active material and the iron phosphate positive electrode active material. Examples of the other positive electrode active material include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, LiNi 1-v-w Co v Al w O2 (0≦v≦1, 0≦w≦1) and other transition metal oxides; compounds with an olivine structure such as LiAPO4 (A=Mn, Ni, Co); solid-solution materials incorporating multiple transition metals (solid solutions of electrochemically inactive layered Li2MnO3 and electrochemically active layered LiMO2 (M=Co, Ni, and other transition metals); LiCo x Mn 1-x O2(0≦x≦1);LiNi x Mn 1-x O2 (0≦x≦1); compounds having a fluorinated olivine structure such as Li2APO4F (A=Fe, Mn, Ni, Co); sulfur, etc. can be used.

[0079] From the viewpoint of improving the output characteristics and electrical characteristics of the secondary battery, the content of the positive electrode active material (the total content of each when multiple positive electrode active materials are included) is, relative to 100 mass% of the total amount of the components contained in the positive electrode composite, preferably 75 mass% or more, more preferably 85 mass% or more, even more preferably 90 mass% or more, and is preferably 99 mass% or less, more preferably 98 mass% or less, even more preferably 95 mass% or less.

[0080] The method of forming (coating) an electrode (negative electrode or positive electrode, the same applies below) is not particularly limited, and examples thereof include (1) a method of coating (and drying) an electrode mixture on an electrode current collector using a conventional coating method (e.g., a doctor blade method, etc.), (2) a method of immersing (and drying) an electrode current collector in an electrode mixture, (3) a method of bonding (e.g., bonding via a conductive adhesive) a sheet formed of an electrode mixture to an electrode current collector and pressing (and drying), (4) a method of coating or casting an electrode mixture to which a liquid lubricant has been added onto an electrode current collector, forming it into a desired shape, and then removing the liquid lubricant (and then stretching in a uniaxial or multiaxial direction), and (5) a method of slurrying an electrode mixture (or a solid content forming an electrode mixture layer) with an electrolyte, transferring the electrode mixture in a semi-solid state to a current collector (electrode current collector), and using it as an electrode (electrode) without drying. Incidentally, the electrode mixture layer may be dried or pressed after formation or application (coating), as necessary.

[0081] (Separator) The non-aqueous electrolyte secondary battery may include a separator. The separator is disposed so as to separate the positive electrode from the negative electrode. There is no particular limitation on the separator, and any conventionally known separator may be used in the present disclosure. Specific examples of the separator include porous sheets made of polymers capable of absorbing and retaining non-aqueous electrolyte (e.g., polyolefin-based microporous separators and cellulose-based separators), non-woven fabric separators, and porous metal bodies.

[0082] Examples of the material for the porous sheet include polyethylene, polypropylene, and a laminate having a three-layer structure of polypropylene / polyethylene / polypropylene.

[0083] Examples of materials for the nonwoven fabric separator include cotton, rayon, acetate, nylon, polyester, polypropylene, polyethylene, polyimide, aramid, glass, etc., and depending on the required mechanical strength, etc., the above-mentioned materials may be used alone or in combination of two or more types.

[0084] (Battery exterior materials) A battery element including a positive electrode, a negative electrode, and a non-aqueous electrolyte (and further a separator) is usually housed in a battery exterior material to protect the battery element from external impacts, environmental deterioration, etc., during use of the battery. There are no particular limitations on the material of the battery exterior material, and any of the conventionally known exterior materials can be used.

[0085] If necessary, the battery exterior material may contain expanded metal, an overcurrent protection element such as a fuse or a PTC element, lead plates, etc. to prevent pressure rise inside the battery and overcharging and discharging.

[0086] The shape of the battery (lithium ion secondary battery, etc.) is not particularly limited, and any of the conventionally known shapes can be used, such as cylindrical, square, laminated, coin, large, etc. When used as a high-voltage power source (several tens of volts to several hundreds of volts) for mounting on electric vehicles, hybrid electric vehicles, etc., it can also be made into a battery module consisting of individual batteries connected in series.

[0087] The rated charging voltage of a secondary battery (lithium ion secondary battery, etc.) is not particularly limited, but when the secondary battery has a positive electrode containing at least one of a ternary positive electrode active material and an iron phosphate positive electrode active material as a main component, it may be, for example, 3.6 V or more, and when the secondary battery has a positive electrode containing a ternary positive electrode active material as a main component, it may be preferably 4.0 V or more, more preferably 4.1 V or more, and even more preferably 4.2 V or more. The higher the rated charging voltage, the higher the energy density can be, but from the viewpoint of safety, etc., the rated charging voltage may be, for example, 4.6 V or less (e.g., 4.5 V or less).

[0088] <Manufacturing method of non-aqueous electrolyte secondary battery> A non-aqueous electrolyte secondary battery can be easily produced, for example, by stacking a positive electrode and a negative electrode (with a separator between them as necessary), placing the resulting laminate in a battery exterior material, injecting a non-aqueous electrolyte into the battery exterior material, and sealing it.

[0089] As described above, the nonaqueous electrolyte secondary battery according to this embodiment uses a Si-based negative electrode and a carbonate-containing electrolyte solution containing LiFSI and a carbonate. In the above configuration, the effect of improving the cycle characteristics, low-temperature charging characteristics, and high-temperature volume expansion characteristics by intentionally dissolving a carbonate in a nonaqueous electrolyte solution containing LiFSI is higher than the effect of improving the cycle characteristics, low-temperature charging characteristics, and high-temperature volume expansion characteristics by dissolving a carbonate in a LiPF6-based nonaqueous electrolyte solution not containing LiFSI. In particular, the effect of improving the low-temperature charging characteristics is significantly exhibited. EXAMPLES

[0090] The present disclosure will be described below based on examples. Note that the present disclosure is not limited to the following examples, and the following examples can be modified or changed based on the spirit of the present disclosure, and are not excluded from the scope of the present disclosure.

[0091] <Example 1 Series> <Production of positive electrodes> LiNi as a ternary positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811, manufactured by Beijing Toben Co., Ltd.), acetylene black (manufactured by Denka, Denka Black, the same applies below), graphite (manufactured by Nippon Graphite, SP270), and polyvinylidene fluoride (PVdF, manufactured by Kureha Corporation, L♯1120) were weighed out in a composition (mass) ratio of 100:3:3:3, and dispersed in N-methyl-2-pyrrolidone (NMP, commercially available product) to prepare a slurry. The slurry was applied to one side of an aluminum foil (coating weight 15.7 mg / cm2). 2 ) and dried, and then roll pressed to prepare a positive electrode.

[0092] <Production of negative electrodes> (Negative electrode 1) A water-based slurry was prepared with natural graphite (commercial product, the same applies below), SiC (commercial product, the same applies below), carbon fiber (VGCF, Showa Denko K.K., the same applies below), acetylene black, styrene butadiene rubber (SBR, commercial product, the same applies below), and carboxymethyl cellulose (CMC, commercial product, the same applies below) in a composition (mass) ratio of 90:10:0.0125:0.25:3:0.98125. The slurry was applied to one side of copper foil (coating weight 6.37 mg / cm2). 2 ), dried, and then roll-pressed to prepare Negative Electrode 1 (SiC content: 10% by mass relative to 100% by mass of the total amount of negative electrode active materials).

[0093] (Negative electrode 2) A water-based slurry was prepared with natural graphite, SiC, VGCF, acetylene black, SBR, and CMC in a composition (mass) ratio of 85:15:0.0125:0.25:3:0.98125. The slurry was applied to one side of a copper foil (coating weight 5.74 mg / cm). 2 ), dried, and then roll-pressed to prepare negative electrode 2 (SiC content: 15% by mass relative to 100% by mass of the total amount of negative electrode active materials).

[0094] (Negative electrode 3) A water-based slurry was prepared with natural graphite, SiC, VGCF, acetylene black, SBR, and CMC in a composition (mass) ratio of 75:25:0.0125:0.25:3:0.98125. The slurry was applied to one side of a copper foil (coating weight 4.43 mg / cm). 2 ), dried, and then roll-pressed to prepare Negative Electrode 3 (SiC content: 25% by mass relative to 100% by mass of the total amount of negative electrode active materials).

[0095] (Negative electrode 4) An aqueous slurry was prepared with SiO (manufactured by BTR, product number: BSO-1, discharge capacity 1500 mAh / g), VGCF, acetylene black, SBR, and CMC in a composition (mass) ratio of 100:0.0125:0.25:3:0.98125. The slurry was applied to one side of a copper foil (coating weight 2.12 mg / cm). 2), dried, and then roll-pressed to prepare Negative Electrode 4 (SiO content: 100% by mass relative to 100% by mass of the total amount of negative electrode active materials).

[0096] (Negative electrode 5) An aqueous slurry was prepared with SiC (manufactured by IOPSILION, discharge capacity 1500 mAh / g), VGCF, acetylene black, SBR, and CMC in a composition (mass) ratio of 100:0.0125:0.25:3:0.98125. The slurry was applied to one side of a copper foil (coating weight 2.12 mg / cm). 2 ), dried, and then roll-pressed to prepare Negative Electrode 5 (SiC content: 100% by mass relative to 100% by mass of the total amount of negative electrode active materials).

[0097] <Production of non-aqueous electrolyte> [Preparation process] In the following description, a nonaqueous electrolyte in which no carbonate component (CO2 in the embodiment) is intentionally dissolved is referred to as a "reference electrolyte." The reference electrolyte is obtained without going through the dissolving step (before the dissolving step), and may contain carbonate components in the raw materials or carbonate components that are unavoidably dissolved.

[0098] (Reference electrolyte 1) A reference electrolyte 1 (LiFSI content: 50 mol%) was prepared by dissolving an electrolyte salt of a mixed salt composition (electrolyte composition 1) containing 0.6 mol / L (M) LiFSI (manufactured by Nippon Shokubai Co., Ltd., the same below) and 0.6 M LiPF6 (manufactured by Stella Chemifa Co., Ltd., the same below) in an electrolyte solvent of a mixed solvent (manufactured by Kishida Chemical Co., Ltd.) with a composition of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3: 7 (volume ratio).

[0099] (Reference electrolyte 2) Reference electrolyte 2 (LiFSI content: 16.7 mol%) was prepared in the same manner as reference electrolyte 1, except that the electrolyte salt was changed to a mixed salt composition (electrolyte composition 2) containing 0.2 M LiFSI and 1 M LiPF6.

[0100] (Reference electrolyte 3) Reference electrolyte 3 (LiFSI content: 4.2 mol%) was prepared in the same manner as reference electrolyte 1, except that the electrolyte salt was changed to a mixed salt composition containing 0.05 M LiFSI and 1.15 M LiPF6 (electrolyte composition 3).

[0101] (Reference electrolyte 4) Reference electrolyte 4 (LiFSI content: 0 mol%) was prepared in the same manner as reference electrolyte 1, except that the electrolyte salt was changed to a single salt composition (electrolyte composition 4) containing only 1.2 M LiPF6.

[0102] (Reference electrolyte 5) Reference electrolyte 5 (LiFSI content: 100 mol%) was prepared in the same manner as reference electrolyte 1, except that the electrolyte salt was changed to a single salt composition containing only 1.2 M LiFSI (electrolyte composition 5).

[0103] [Dissolution process (pressurization process / replacement process)] Each of the standard electrolyte solutions 1 to 5 obtained in the above preparation process was placed in an autoclave with the lid of the storage container open, and the inside of the autoclave was pressurized to 3 atmospheres with CO2 and released to 1.5 atmospheres. This process was repeated three times to replace the inside of the autoclave with CO2. After the replacement, the pressure was increased to 3 atmospheres with CO2 and the autoclave was left for 30 minutes. Through the above process, each of the CO2-dissolved electrolyte solutions 1 to 5 was prepared by intentionally dissolving (dissolving) CO2 in each of the standard electrolyte solutions 1 to 5.

[0104] [Measurement of dissolved CO2] The amount of dissolved CO2 in each of the CO2-dissolved electrolytes 1 to 5 was quantified by the following method using gas chromatography (apparatus: GC-2010 plus, manufactured by Shimadzu Corporation; column: Micropacked ST, manufactured by Shinwa Kako Co., Ltd.).

[0105] (Gas Chromatography Measurement Conditions) When measuring by gas chromatography, the nonaqueous electrolyte or the calibration curve solution was directly put into the gas chromatography apparatus in a state where the apparatus was purged with nitrogen (under a nitrogen atmosphere) so as not to mix air into the measurement system. The specific measurement conditions for gas chromatography are as follows. Column temperature program: Hold at 37°C (for 2.5 minutes from the start) ⇒ 37°C to 250°C (heat up at 20°C / min) ⇒ 250°C to 270°C (heat up at 15°C / min) ⇒ Hold at 270°C (for 5.42 minutes). - Vaporizer temperature: 260℃. Detector temperature: 300℃(BID). Carrier gas: Helium (column flow rate 1.33 mL / min). Injection volume: 1 μL (split method, split ratio: 5.0.

[0106] (Method for quantifying dissolved CO2) A calibration curve showing the relationship between the mass of CO2 injected and the peak area of ​​CO2 gas was created. Next, each of the CO2-dissolved electrolytes 1-5 was analyzed by gas chromatography. Finally, the amount of CO2 dissolved in each of the CO2-dissolved electrolytes 1-5 was quantified by the internal standard method.

[0107] As a result of quantification under the above measurement conditions and quantification method, the amount of dissolved CO2 in each of the standard electrolyte solutions 1 to 5 was 10 ppm by mass. The amount of dissolved CO2 in each of the CO2-dissolved electrolyte solutions 1 to 5 was 3,500 ppm by mass. Each of the CO2-dissolved electrolyte solutions 1 to 5 was diluted with the corresponding standard electrolyte solutions 1 to 5 (having the same electrolyte composition) to prepare CO2-dissolved electrolyte solutions with different amounts of dissolved CO2.

[0108] <Manufacturing of laminated lithium-ion batteries (non-aqueous electrolyte secondary batteries)> Positive electrode with an effective area of ​​12cm 2 The negative electrodes 1 to 5 shown in the table below were cut into pieces with an effective area of ​​13.44 cm2, and the polarity lead was welded using an ultrasonic welding machine. 2The battery was cut into pieces and the polarity leads were ultrasonically welded. These were placed opposite each other with a 25μ polyethylene (PE) separator and sealed on three sides with a laminate exterior to create a non-injected cell. 700μmL of each electrolyte shown in the table below was injected into one of the unsealed sides of the non-injected cell to create a 30mAh laminated lithium ion battery (non-aqueous electrolyte secondary battery). After the electrolyte was injected, the battery was charged at a constant current of 3 mA for 3 hours and then stored at 25°C for 48 hours. After that, it was charged under the following conditioning condition 1 to complete the evaluation battery. (Conditioning condition 1) 1st cycle: Charging: 3mA, constant current constant voltage charging at 4.2V, termination at 0.3mA ⇒ Discharge: Discharge at 6mA, terminate at 2.75V. After one cycle, one piece of the laminate was cleaved and vacuum sealed again to degas the laminate. After degassing, the following conditioning was performed for the second and subsequent cycles. 2nd cycle: Charging: 15mA, constant current constant voltage charging at 4.2V, termination at 0.6mA ⇒ Discharge: Discharge at 6mA, terminate at 2.75V. 3rd cycle: Charging: 15mA, constant current constant voltage charging at 4.2V, termination at 0.6mA ⇒ Discharge: Discharge at 30mA, terminate at 2.75V. 4th cycle: Charging: 15mA, constant current constant voltage charging at 4.2V, termination at 0.6mA ⇒ Discharge: Discharge at 60mA, terminate at 2.75V.

[0109] Battery evaluation The evaluation battery prepared above was used to evaluate the following battery performance.

[0110] [45℃ cycle (cycle characteristics)] (Cycle capacity retention rate) Using the conditioned battery, a cycle test was performed at 45° C. for 500 or 50 cycles under the following cycle condition 1. The capacity retention rate after the cycles was calculated using the following formula (1): [Number 1] Cycle capacity retention rate (%) = (1C capacity at 500 or 50th cycle / 1C capacity at 1st cycle) × 100 (1) The cycle capacity retention rate was calculated based on the above formula. A larger value for the cycle capacity retention rate indicates better cycle characteristics. [Cycle condition 1] Charging: 4.2V, constant current / voltage charging at 1C (30mA), stopping at 0.02C (0.6mA), resting for 5 minutes. Discharge: Constant current discharge at 1C (30mA), terminate at 2.75V, rest discharge for 5 minutes.

[0111] (Improvement rate of cycle capacity retention) When the cycle capacity retention rate of the battery containing each of the standard electrolytes 1 to 5 was set to 100%, the improvement rate (%) of the cycle capacity retention rate of the battery containing the corresponding CO2-dissolved electrolytes 1 to 5 (electrolytes in which a predetermined amount of CO2 was dissolved in each of the standard electrolytes 1 to 5 having the same electrolyte composition; the same applies below) was calculated. A higher improvement rate of the cycle capacity retention rate means a higher improvement effect of the cycle characteristics.

[0112] [Low temperature charging] (low temperature charging capacity) After conditioning, the battery was discharged at a constant current of 6 mA at 25°C with a termination voltage of 2.75 V, and then left to stand at -20°C for 3 hours before being charged at a constant current of 30 mA with a termination voltage of 4.2 V at -20°C. The charge capacity at this time was measured. Note that the higher the low-temperature charge capacity, the better the low-temperature charge characteristics.

[0113] (Improvement rate of low temperature charging capacity) The improvement rate (%) of the low-temperature charging capacity of the battery containing each of the standard electrolytes 1 to 5 was calculated based on the low-temperature charging capacity of the battery containing the corresponding CO2-dissolved electrolytes 1 to 5. The higher the improvement rate of the low-temperature charging capacity, the greater the improvement effect of the low-temperature charging characteristics.

[0114] [Volumetric expansion at high temperatures] (Volume increase rate after storage at 80℃ for 7 days) The volume of the battery after conditioning (volume before storage) was measured by the Archimedes method. Then, the battery was stored at 80°C for 7 days, and the volume of the battery (volume after storage) was measured by the Archimedes method in the same manner. The volume increase rate after storage at 80°C for 7 days (after high temperature durability) relative to the volume before storage was calculated using the following formula (2): [Number 2] Volume increase rate after high temperature durability (%) = (volume after storage / volume before storage) × 100 (2) The volume increase rate was calculated based on the following. The smaller the volume increase rate, the smaller (more suppressed) the high-temperature volume expansion.

[0115] (Improvement rate of volume increase after high temperature durability) The improvement rate (%) of the volume increase rate after high-temperature endurance of the battery containing each of the standard electrolytes 1 to 5 was calculated by assuming the volume increase rate after high-temperature endurance of the battery containing the corresponding CO2-dissolved electrolytes 1 to 5. The smaller the improvement rate of the volume increase rate after high-temperature endurance, the greater the improvement effect of the high-temperature volume expansion characteristics.

[0116] [Table 1]

[0117] [Table 2]

[0118] <Summary of Example 1 Series> When comparing electrolyte compositions 1 to 3 (1 or 2) in batteries equipped with the same Si-based negative electrode, the higher the LiFSI concentration, the greater the improvement in cycle capacity retention, low-temperature charge capacity, and volume increase rate after high-temperature endurance when 20 ppm or more of CO2 (carbonate component) was dissolved in the non-aqueous electrolyte. In the battery equipped with the negative electrode 1, the battery equipped with the CO2-dissolved electrolyte containing LiFSI (electrolyte composition 1-3) had higher improvement rates in all three of the above points compared to the battery equipped with the CO2-dissolved electrolyte containing only LiPF6 without LiFSI (electrolyte composition 4). In other words, it was found that the CO2-dissolved electrolyte battery including LiFSI has a higher improvement effect in cycle characteristics, low-temperature charging characteristics, and high-temperature volume expansion characteristics due to dissolving CO2 in the non-aqueous electrolyte compared to the battery equipped with the conventional LiPF6-based CO2-dissolved electrolyte. In particular, the improvement effect in low-temperature charging capacity was remarkable. Comparing negative electrodes 1 to 5 in batteries equipped with nonaqueous electrolytes of the same electrolyte composition, the higher the content of SiC or SiO in the negative electrode active material, the greater the improvement effect of the above three characteristics due to dissolving CO2 in the nonaqueous electrolyte.

[0119] <Example 2 Series> The ternary positive electrode active material is LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622, manufactured by Beijing Toben Co., Ltd.) and the coating weight was increased to 19.5 mg / cm 2 A positive electrode was produced in the same manner as in Example 1 series, except that the positive electrode was changed to the above. A battery for evaluation was produced and evaluated in the same manner as in Example 1 series, except that the positive electrode was changed to the above.

[0120] [Table 3]

[0121] <Summary of Example 2 Series> In Example 2 series, in which the ternary positive electrode active material was changed to NCM622, the same improvement effect as in Example 1 series was confirmed.

[0122] <Example 3 Series> The ternary positive electrode active material is LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523, manufactured by Beijing Toben Co., Ltd.) and the coating weight was increased to 19.5 mg / cm 2A positive electrode was produced in the same manner as in Example 1 series, except that the positive electrode was changed to the above. A battery for evaluation was produced and evaluated in the same manner as in Example 1 series, except that the positive electrode was changed to the above.

[0123] [Table 4]

[0124] <Summary of Example 3 Series> In Example 3 series, in which the ternary positive electrode active material was changed to NCM523, the same improvement effect as in Example 1 series was confirmed.

[0125] <Example 4 Series> The ternary positive electrode active material is (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM111, Umicore), and the coating weight was changed to 19.7 mg / cm 2 A positive electrode was produced in the same manner as in Example 1 series, except that the positive electrode was changed to the above. A battery for evaluation was produced and evaluated in the same manner as in Example 1 series, except that the positive electrode was changed to the above.

[0126] [Table 5]

[0127] <Summary of Example 4 Series> In Example 4 series, in which the ternary positive electrode active material was changed to NCM111, the same improvement effect as in Example 1 series was confirmed.

[0128] <Considerations regarding Examples 1 to 4 Series> In secondary batteries with the same Si-based negative electrodes, when comparing the positive electrodes, the difference in the improvement rate of the cycle capacity retention rate and the low-temperature charging capacity between the battery using LiFSI and CO2 in combination (electrolyte composition 1-3) and the battery using LiPF6 and CO2 in combination (electrolyte composition 4) became higher as the content of Ni in the positive electrode increased (Examples 1-3 series compared to Example 4 series). The reason for this is unclear, but a sulfur-based coating by LiFSI and a Li2CO3 coating by CO2 are formed on the positive electrode, and these two coatings protect the positive electrode, but in the positive electrode where the content of Ni is high and the volume change due to expansion and contraction is large, a composite coating of sulfur and Li2CO3 is formed, and it is assumed that this composite coating has a strong influence on the protection of the positive electrode. -Comparing negative electrodes 1 to 5, in batteries equipped with non-aqueous electrolytes and positive electrodes of the same electrolyte composition, the higher the percentage of Si in the negative electrode, the higher the improvement in cycle capacity retention, low-temperature charge capacity, and volume increase rate after high-temperature durability due to dissolving CO2 in the non-aqueous electrolyte. This indicates that CO2 mainly acts to improve the durability of Si in the Si-based negative electrode. Although the details of this mechanism are unclear, it is thought that a composite coating of fluorosulfonylimide (FSI) anions and lithium carbonate produced by the reaction of CO2 with Li is formed on the Si-based negative electrode, and that this composite coating acts as a stable coating for Si to protect it.

[0129] <Example 5 Series> <Production of positive electrodes> LiFePO4 (commercial product) as an iron phosphate-based positive electrode active material, acetylene black, and PVdF (Kureha Corporation, L♯7208) were weighed in a composition (mass) ratio of 100:9:6 and dispersed in NMP to prepare a slurry. The prepared slurry was coated on one side of an aluminum foil (coating weight 24.3 mg / cm 2 ) and dried, and then roll pressed to prepare a positive electrode.

[0130] <Manufacturing of laminated lithium-ion batteries (non-aqueous electrolyte secondary batteries)> A 30 mAh laminated lithium ion battery (nonaqueous electrolyte secondary battery) was produced in the same manner as in Example 1 series, except that the positive electrode was changed to the one obtained above. After the electrolyte was injected, the battery was charged at a constant current of 3 mA for 3 hours and then stored at 25°C for 48 hours. After that, it was charged under the following conditioning condition 2 to complete the evaluation battery. (Conditioning condition 2) 1st cycle: Charging: 3mA, constant current constant voltage charging at 3.6V, termination at 0.3mA ⇒ Discharge: Discharge at 6mA, terminate at 2.0V. After one cycle, one piece of the laminate was cleaved and vacuum sealed again to degas the laminate. After degassing, the following conditioning was performed for the second and subsequent cycles. 2nd cycle: 15mA, constant current constant voltage charge at 3.6V, terminated at 0.6mA ⇒ Discharge: Discharge at 6mA, terminate at 2.0V. 3rd cycle: Charging: 15mA, constant current constant voltage charging at 3.6V, termination at 0.6mA ⇒ Discharge: Discharge at 30mA, terminate at 2.0V. 4th cycle: 15mA, constant current constant voltage charge at 3.6V, terminated at 0.6mA ⇒ Discharge: Discharge at 60mA, terminate at 2.0V.

[0131] Battery evaluation Using the evaluation battery prepared above, the battery performance was evaluated in the same manner as in Example 1 series, except for the 45° C. cycle shown below.

[0132] [45℃ cycle (cycle characteristics)] (Cycle capacity retention rate) The capacity retention rate and its improvement rate were calculated in the same manner as in Example 1 series, except that the cycle condition was changed to the following cycle condition 2. [Cycle condition 2] Charging: 3.6V, constant current / voltage charging at 1C (30mA), stopping at 0.02C (0.6mA), resting for 5 minutes. Discharge: Constant current discharge at 1C (30mA), terminate at 2.0V, rest discharge for 5 minutes.

[0133] [Table 6]

[0134] <Summary of Example 5 Series> In the Example 5 series, in which the ternary positive electrode active material was changed to the iron phosphate positive electrode active material LiFePO4, the same improvement effect as in the Example 1 series was confirmed. The improvement effect of dissolved CO2 was also confirmed in batteries using a nonaqueous electrolyte with a simple salt composition containing only LiFSI (electrolyte composition 5), and this improvement effect was greater than that of a nonaqueous electrolyte with a simple salt composition containing only LiPF6 (electrolyte composition 4).

Claims

1. LiN (FSO 2 ) 2 and carbon dioxide (CO 2 ), carbon monoxide (CO), bicarbonate ion (HCO 3 - ) and carbonate ion (CO 3 2- a non-aqueous electrolyte solution having at least one carbonate component dissolved therein, a negative electrode containing at least one material selected from the group consisting of Si, a Si alloy, and SiO as a negative electrode active material; A positive electrode; A non-aqueous electrolyte secondary battery, wherein the total dissolved amount of the carbonate components is 20 ppm by mass or more relative to 100% by mass of the total amount of the components contained in the non-aqueous electrolyte.

2. LiN (FSO 2 ) 2 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the content of is 1 mol % or more with respect to 100 mol % in total of the electrolyte salts contained in the nonaqueous electrolyte.

3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the content of at least one selected from the group consisting of Si, a Si alloy, and SiO is 5% by mass or more relative to 100% by mass of a total amount of the negative electrode active material.

Citation Information

Patent Citations

  • Lithium secondary battery and its manufacturing method

    JP2005190977A

  • Lithium secondary battery

    JP2006196435A

  • Lithium rechargeable battery and method for manufacturing the same

    WO2007114168A1